1D/2D Cobalt‐Based Nanohybrids as Electrocatalysts for Hydrogen Generation. (20th February 2020) - Navarro‐Pardo, Fabiola; Liu, Jiabin; Abdelkarim, Omar; Selopal, Gurpreet S.; Yurtsever, Aycan; Tavares, Ana C.; Zhao, Haiguang; Wang, Zhiming M.; Rosei, Federico
Abstract: The synergistic effects derived from optimizing the chemical and structural features of electrocatalysts permit them to attain remarkable activity and stability. Herein, 1D/2D cobalt‐based nanohybrid (CoNH) electrodes are developed; the structural design consists of Co3 O4 electrospun nanoribbons (NRs) deposited onto a carbon fiber paper substrate where Co3 O4 nanosheets are subsequently grown via an electrodeposition step and UV/ozone treatment. The content of noncovalently functionalized carbon nanotubes within the Co3 O4 NRs is first tuned to enhance their charge transfer properties and mechanical stability. The electrocatalytic activity of the electrodes is further improved by a phosphorus modification of the 1D NRs, resulting in the formation of NaCoPO4 . The optimized 1D/2D CoNH electrode, i.e., ED‐0.09 wt% fCNTs/P‐CoNHs, displays a similar performance to that of platinum in 0.25 m Na2 S/0.35 m Na2 SO3 (Tafel slope ≈102 mV dec −1 for the former and ≈96 mV dec −1 for the latter) and outstanding stability for up to 48 h. The versatility and high activity of this electrode is also demonstrated according to tests in a conventional water splitting system (cell voltage 1.55V, to produce 10 mA cm −2 ) and a solar‐driven electrolyzer (1 m KOH). Abstract : High electrocatalytic activity is obtained by tuning the composition and architectural design of 1D/2D cobalt‐nanohybrids. Incorporation of functionalized carbon nanotubes and phosphorus modification within 1D electrospun nanoribbons, followed by the electrodeposition of 2D nanosheets results in enhanced intrinsic activity, improved charge transfer, and remarkable stability toward hydrogen generation in alkaline media.